Use of constructed wetlands for treatment of milk cooling tank wastewater: removal of BOD and COD - Saraiva, Claudety Barbosa (2016)
The objective of this study was to use constructed wetlands of surface horizontal flow for wastewater treatment of milk cooling tank, assessing their respective efficiencies depending on the removal rates of BOD and COD. All treatments reached a relatively high efficiency in the removal of BOD, but did not meet the standard established by legislation for discharge of effluents into water bodies. However, all treatments showed COD in the limit established by legislation.